Impact of a simulated practice program in the construction of self-confidence for intervention in emergencies and association with knowledge and performance - Batista, Rui Carlos Negrão (2017)
The objective was to assess the impact of a simulated practice program on the construction of self-confidence for intervention in emergencies and its association with knowledge and performance. This is a quasi-experimental study without control group, with assessment before and after a 15-hour simulated practice program, in nursing students. The students' self-confidence increased significantly as a result of simulated practice with positive and statistically significant association between practical assessment and self-confidence levels.